1996
DOI: 10.1097/00005344-199604000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of the Specific Endothelin-1 Antagonist BQ610 on Mechanical Function and Energy Metabolism During Ischemia/Reperfusion Injury in Isolated Perfused Rat Hearts

Abstract: Endothelin-1 (ET-1) has been suggested to be involved in the pathophysiology of ischemia/reperfusion injury, but direct proof for this is still sparse. We tested whether protection of high-energy phosphate metabolism contributes to the beneficial effects of ETA receptor antagonists during ischemia/reperfusion. In isolated, buffer-perfused rat hearts, isovolumic function was measured by a left ventricular (LV) balloon, and 31P nuclear magnetic resonance spectra were continuously recorded. Two protocols were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
1
13
1
Order By: Relevance
“…[12][13][14][37][38][39] In the present study, we also observed that ABT-627 alone and the combination of ABT-627/A-192621 had similar protective effects against postischemic cardiac dysfunction in rat hearts. Previous studies have demonstrated that ET-1 mRNA expression and its peptide production are increased in cardiomyocytes subjected to ischemia 40 and that plasma ET-1 levels are elevated in both humans 5 and experimental animals 11,41 with myocardial infarction.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…[12][13][14][37][38][39] In the present study, we also observed that ABT-627 alone and the combination of ABT-627/A-192621 had similar protective effects against postischemic cardiac dysfunction in rat hearts. Previous studies have demonstrated that ET-1 mRNA expression and its peptide production are increased in cardiomyocytes subjected to ischemia 40 and that plasma ET-1 levels are elevated in both humans 5 and experimental animals 11,41 with myocardial infarction.…”
Section: Discussionsupporting
confidence: 82%
“…Actually, a monoclonal antibody against ET-1 can reduce infarct size in rats after coronary artery ligation and reperfusion. 11 Moreover, both selective ET A receptor antagonists and nonselective ET A /ET B receptor antagonists exhibited protective effects against postischemic cardiac dysfunction, [12][13][14] although others failed to observe such beneficial effects. 15 Norepinephrine (NE) release from cardiac sympathetic nerve endings occurs mainly by 2 pathways: Ca 2Ļ© -dependent exocytotic release and Ca 2Ļ© -independent carrier-mediated release via activation of the NE transporter (NET) in the outward direction.…”
mentioning
confidence: 99%
“…It has been mentioned that ET-1 plays a critical role in heart injury mostly through the activation of ET A receptors. 7,9,10,14 However, our present data showed that ET-1 generated from exogenously applied big ET-1 preferentially acts on ET B receptors rather than ET A receptors in the postischemic heart. In the present study, we have chosen the doses of exogenous big ET-1 in the ranges from 0.1 to 1 nM.…”
Section: Discussioncontrasting
confidence: 64%
“…[7][8][9][10]14 In addition, we obtained evidence that exogenously applied ET-1 to the ischemic heart further enhanced the NE overflow and exacerbates the postischemic cardiac dusfunction. 10 In the present study, we expected that exogenously applied big ET-1 would cause deterioration of cardiac function following the global ischemia and reperfusion, because exogenously applied big ET-1 exerts qualitatively similar effects to ET-1, in the cardiovascular system in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation